(untitled) (Bangladesh Journal of Pharmacology, 2015)
This study was aimed to evaluate antimicrobial mode of action of Ginkgo biloba leaf essential oil against foodborne pathogenic bacteria. Gas-chromatography and mass-spectrometric analysis determined 34 different compounds, representing 95.45% of the total oil. The G. biloba leaf essential oil (1,000 µg/disc) showed potential antibacterial effect as diameters of inhibition zones (12.0 ± 0.4-18.0 ± 1.2 mm) along with minimum inhibitory and minimum bactericidal concentration values ranging of 250-1,000 µg/mL. Also the G. biloba leaf essential oil had potential inhibitory effect on the cell viability of the tested pathogens. The scanning electron microscopic analysis using G. biloba leaf essential oil showed considerable morphological alterations on the cell wall of tested pathogens. The oil revealed its mode of action on membrane integrity as confirmed by release of extracellular ATP, increase of 260-nm absorbing materials and increased leakage of potassium ions against foodborne pathogenic bacteria.